LOW-COST SYSTEM FOR THE RAPID DIAGNOSIS OF SLEEP APNEA, CAUSED BY THE COVID-19 PANDEMIC - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Sleep Apnea is one of the lesser-known pathologies that many people do not take into consideration when conducting a medical check-up, but it is one of the indicators of levels of fatigue, stress that are shown by lack of sleep, bad sleeping habits or other silent indicators such as problems breathing when sleeping, snoring among others. In these moments of confinement in our homes caused by COVID-19, where most of them cannot work, study or do other activities in person, certain levels of stress begin to emerge in both adults and children, these manifestations are shown in problems at bedtime. In the present work an analysis is carried out on the possible consequences of Sleep Apnea, as well as a methodology based on the use of Weareable Devices is presented, to be able to analyze how our way of sleeping is and thus be attentive to any changes in the demonstrations at bedtime. My methodology presents some previous steps for the configuration of the device, the acquisition of information when we are sleeping and the analysis of the results of the signals captured at the time of sleep, the analysis is very intuitive. In this way we can know if we are changing habits when sleeping.